France : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper reviews business investment patterns in France during the crisis. The main motivation is to explore whether investment has recently evolved in line with established determinants or displayed somewhat unconventional dynamics. This paper addresses three distinct questions. First, has recent investment behavior essentially been consistent with past trends or is there any discernible structural break as a result of the crisis. Second, what drove the contraction in investment during the crisis. Third, what is the investment outlook and can a swift and strong rebound going forward be expected. The paper presents main results and the outlook for investment.